2021
DOI: 10.3389/fncel.2021.746631
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuins as Potential Therapeutic Targets for Mitigating Neuroinflammation Associated With Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most common neurodegenerative disorder, which is associated with memory deficit and global cognitive decline. Age is the greatest risk factor for AD and, in recent years, it is becoming increasingly appreciated that aging-related neuroinflammation plays a key role in the pathogenesis of AD. The presence of β-amyloid plaques and neurofibrillary tangles are the primary pathological hallmarks of AD; defects which can then activate a cascade of molecular inflammatory pathways in gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 214 publications
(243 reference statements)
1
17
0
Order By: Relevance
“…Betaine shows anti-inflammatory effects both by inhibiting proinflammatory IL-1β production and IL-1β release (Xia et al, 2018;Zhao et al, 2018). Hence, betaine therapy may be beneficial not only in liver disease but also in other health conditions which are linked with inflammation, such as obesity, heart diseases, and Alzheimer's disease (Mathieu et al, 2010;Fernando and Wijayasinghe, 2021). Veskovic et al (2019) recently showed that the oral betaine treatment not only restored the methionine-Hcy cycle, but also reduced hepatosteatosis, oxidative stress (via increasing glutathione levels and antioxidant enzyme activities), inflammation (via induction of anti-inflammatory IL-10 and decreasing proinflammatory TNF and IL-6 expression), and…”
Section: Non-alcoholic Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Betaine shows anti-inflammatory effects both by inhibiting proinflammatory IL-1β production and IL-1β release (Xia et al, 2018;Zhao et al, 2018). Hence, betaine therapy may be beneficial not only in liver disease but also in other health conditions which are linked with inflammation, such as obesity, heart diseases, and Alzheimer's disease (Mathieu et al, 2010;Fernando and Wijayasinghe, 2021). Veskovic et al (2019) recently showed that the oral betaine treatment not only restored the methionine-Hcy cycle, but also reduced hepatosteatosis, oxidative stress (via increasing glutathione levels and antioxidant enzyme activities), inflammation (via induction of anti-inflammatory IL-10 and decreasing proinflammatory TNF and IL-6 expression), and…”
Section: Non-alcoholic Liver Diseasementioning
confidence: 99%
“…Furthermore, TMAO-induced activation of the NLRP3 inflammasome, a proinflammatory protein complex, results in increased production of the proinflammatory cytokine IL-1β both in vitro and in vivo , which contributes to endothelial injury ( Chen et al, 2017a ; Boini et al, 2017 ). The activation of NLRP3 inflammasome was found to be associated with increased mitochondrial reactive oxygen species (ROS) generation due to the TMAO-induced downregulation of mitochondrial NAD + -dependent protein deacetylase sirtuin3 (Sirt3) and subsequent inhibition of manganese superoxide dismutase 2 (SOD2) activation ( Rogacev et al, 2012 ; Fernando and Wijayasinghe, 2021 ). These results suggest that high plasma TMAO levels potentially contribute to chronic vascular inflammation and hence to increased incidence of cardiovascular events in patients.…”
Section: Health Implications Of Trimethylamine-n-oxidementioning
confidence: 99%
“…However, inhibition of SIRT2 mitigates α-synuclein toxicity in human neuroglioma cells [ 83 ]. On the other hand, SIRT1, SIRT3, and SIRT6 expression is reduced in the brain of patients with AD [ 84 ]. Moreover, SIRT1 [ 85 ] and SIRT3 [ 86 ] protein concentrations are reduced in the cerebral cortex of individuals with AD.…”
Section: Sirtuinsmentioning
confidence: 99%
“…This coenzyme is essential for SIRTs deacetylation activity. Interestingly, even though SIRT1 mRNA levels increase with age in animal brains, there is deterioration in its enzymatic activity, which is related to the NAD+ decline [ 84 ]. Notably, not all SIRTs are NAD-dependent in the same manner since SIRT1 and SIRT3 have higher Km values than the other SIRTs, meaning that their function is favorable when NAD+ levels are higher [ 176 ]; therefore, increasing NAD+ concentration may restore their enzymatic activity.…”
Section: Sirt Modulationmentioning
confidence: 99%
“…Alzheimer’s disease (AD) is a neurodegenerative disorder, clinically manifesting with a progressive loss of memory and cognitive functions ( Scheltens et al, 2016 ; Fernando and Wijayasinghe, 2021 ). Histopathologic findings in AD patients’ brains usually occur much earlier than clinical manifestations of the disease; they include β -amyloid deposition in the interneural space and accumulation of abnormal, hyperphosphorylated tau proteins within neurons ( Sperling et al, 2011 ; Kumar et al, 2015 ; Hanseeuw et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%